Breuken haakjesregel (reeks 1)

Hoofdmenu Eentje per keer 

Bereken

  1. \(-\left(\frac{2}{-11}\right)+\left(\frac{-10}{11}\right)\)
  2. \(-\left(\frac{-6}{-13}\right)+\left(\frac{4}{-3}\right)\)
  3. \(-\left(\frac{-3}{7}\right)-\left(\frac{10}{-13}\right)\)
  4. \(+\left(\frac{-12}{7}\right)-\left(\frac{-7}{-9}\right)\)
  5. \(+\left(\frac{12}{13}\right)-\left(\frac{-11}{-10}\right)\)
  6. \(-\left(\frac{-3}{-10}\right)-\left(\frac{9}{-14}\right)\)
  7. \(-\left(\frac{-3}{-11}\right)+\left(\frac{-14}{3}\right)\)
  8. \(+\left(\frac{-10}{7}\right)+\left(\frac{3}{11}\right)\)
  9. \(-\left(\frac{13}{11}\right)+\left(\frac{-2}{-15}\right)\)
  10. \(-\left(\frac{-2}{13}\right)+\left(\frac{-8}{-3}\right)\)
  11. \(+\left(\frac{-11}{3}\right)+\left(\frac{-6}{11}\right)\)
  12. \(+\left(\frac{-11}{-14}\right)+\left(\frac{7}{13}\right)\)

Bereken

Verbetersleutel

  1. \(-\left(\frac{2}{-11}\right)+\left(\frac{-10}{11}\right)\\= \frac{2}{11}-\frac{10}{11}\\=\frac{2-10}{11}\\=\frac{-8}{11}\)
  2. \(-\left(\frac{-6}{-13}\right)+\left(\frac{4}{-3}\right)\\= \frac{-6}{13}-\frac{4}{3}\\=\frac{-18}{39}-\frac{52}{39}\\=\frac{-18-52}{39}\\=\frac{-70}{39}\)
  3. \(-\left(\frac{-3}{7}\right)-\left(\frac{10}{-13}\right)\\= \frac{3}{7}+\frac{10}{13}\\=\frac{39}{91}+\frac{70}{91}\\=\frac{39+70}{91}\\=\frac{109}{91}\)
  4. \(+\left(\frac{-12}{7}\right)-\left(\frac{-7}{-9}\right)\\= \frac{-12}{7}-\frac{7}{9}\\=\frac{-108}{63}-\frac{49}{63}\\=\frac{-108-49}{63}\\=\frac{-157}{63}\)
  5. \(+\left(\frac{12}{13}\right)-\left(\frac{-11}{-10}\right)\\= \frac{12}{13}-\frac{11}{10}\\=\frac{120}{130}-\frac{143}{130}\\=\frac{120-143}{130}\\=\frac{-23}{130}\)
  6. \(-\left(\frac{-3}{-10}\right)-\left(\frac{9}{-14}\right)\\= \frac{-3}{10}+\frac{9}{14}\\=\frac{-21}{70}+\frac{45}{70}\\=\frac{-21+45}{70}\\=\frac{24}{70}\\=\frac{12}{35}\)
  7. \(-\left(\frac{-3}{-11}\right)+\left(\frac{-14}{3}\right)\\= \frac{-3}{11}-\frac{14}{3}\\=\frac{-9}{33}-\frac{154}{33}\\=\frac{-9-154}{33}\\=\frac{-163}{33}\)
  8. \(+\left(\frac{-10}{7}\right)+\left(\frac{3}{11}\right)\\= \frac{-10}{7}+\frac{3}{11}\\=\frac{-110}{77}+\frac{21}{77}\\=\frac{-110+21}{77}\\=\frac{-89}{77}\)
  9. \(-\left(\frac{13}{11}\right)+\left(\frac{-2}{-15}\right)\\= \frac{-13}{11}+\frac{2}{15}\\=\frac{-195}{165}+\frac{22}{165}\\=\frac{-195+22}{165}\\=\frac{-173}{165}\)
  10. \(-\left(\frac{-2}{13}\right)+\left(\frac{-8}{-3}\right)\\= \frac{2}{13}+\frac{8}{3}\\=\frac{6}{39}+\frac{104}{39}\\=\frac{6+104}{39}\\=\frac{110}{39}\)
  11. \(+\left(\frac{-11}{3}\right)+\left(\frac{-6}{11}\right)\\= \frac{-11}{3}-\frac{6}{11}\\=\frac{-121}{33}-\frac{18}{33}\\=\frac{-121-18}{33}\\=\frac{-139}{33}\)
  12. \(+\left(\frac{-11}{-14}\right)+\left(\frac{7}{13}\right)\\= \frac{11}{14}+\frac{7}{13}\\=\frac{143}{182}+\frac{98}{182}\\=\frac{143+98}{182}\\=\frac{241}{182}\)
Oefeningengenerator vanhoeckes.be/wiskunde 2022-06-27 08:20:34